Severe vivax malaria trends in the last two years: a study from a tertiary care centre, Delhi, India - Monika Matlani; Loick P. Kojom; Neelangi Mishra; Vinita Dogra; Vineeta Singh (BMC, 2020)
Abstract Background Plasmodium vivax, once considered benign species, is recently being recognised to be causing severe malaria like Plasmodium falciparum. In the present study, the authors report the trends in malaria severity in P. vivax among patients from a Delhi government hospital. The aim of the study was to understand the disease severity and the burden of severe vivax malaria. Methods A hospital based study was carried out from June 2017 to December 2018 at a tertiary care centre from Delhi, India. Patients were tested for malaria using peripheral blood smear (PBS) and/or rapid malaria antigen test (RMAT). The severe and non-severe vivax malaria categorization was done as per the WHO guidelines. Sociodemographic, clinic and paraclinical data were collected from patients and their medical records. Results Of the 205 patients, 177 (86.3%) had P. vivax infection, 22 (10.7%) had P. falciparum infection and six (2.9%) had mixed infection with both the species. Out of 177 P. vivax cases included in this study one or more manifestations of severe malaria was found in 58 cases (32.7%). Severe anaemia (56.9%), jaundice (15%) and significant bleeding (15%) were the most common complications reported in most of patients, along with thrombocytopenia. Conclusions In this study, it is evident that vivax malaria is emerging as the new severe disease in malaria patients, a significant shift in the paradigm of P. vivax pathogenesis. The spectrum of complications and alterations in the laboratory parameters in P. vivax clinical cases also indicate the recent shift in the disease severity.